EpIG‐DB: A database of vascular epiphyte assemblages in the Neotropics. (5th April 2020) - Mendieta‐Leiva, Glenda; Ramos, Flavio N.; Elias, João P. C.; Zotz, Gerhard; Acuña‐Tarazona, Margoth; Alvim, Francine Seehaber; Barbosa, Daniel E. F.; Basílio, Geicilaine A.; Batke, Sven P.; Benavides, Ana María; Blum, Christopher T.; Boelter, Carlos R.; et al.
Abstract: Vascular epiphytes are a diverse and conspicuous component of biodiversity in tropical and subtropical forests. Yet, the patterns and drivers of epiphyte assemblages are poorly studied in comparison with soil‐rooted plants. Current knowledge about diversity patterns of epiphytes mainly stems from local studies or floristic inventories, but this information has not yet been integrated to allow a better understanding of large‐scale distribution patterns. EpIG‐DB, the first database on epiphyte assemblages at the continental scale, resulted from an exhaustive compilation of published and unpublished inventory data from the Neotropics. The current version of EpIG‐DB consists of 463, 196 individual epiphytes from 3, 005 species, which were collected from a total of 18, 148 relevés (host trees and 'understory' plots). EpIG‐DB reports the occurrence of 'true' epiphytes, hemiepiphytes and nomadic vines, including information on their cover, abundance, frequency and biomass. Most records (97%) correspond to sampled host trees, 76% of them aggregated in forest plots. The data is stored in a TURBOVEG database using the most up‐to‐date checklist of vascular epiphytes. A total of 18 additional fields were created for the standardization of associated data commonly used in epiphyte ecology (e.g. by considering different sampling methods). EpIG‐DB currently covers six major biomes across the whole latitudinal range of epiphytes in the Neotropics but welcomes data globally. This novel database provides, for the first time, unique biodiversity data on epiphytes for the Neotropics and unified guidelines for future collection of epiphyte data. EpIG‐DB will allow exploration of new ways to study the community ecology and biogeography of vascular epiphytes. Abstract : Upper right corner, Tillandsia tetrantha Ruiz & Pav. (Photo: Florian A. Werner) and Prosthechea hartwegii (Lindl.) W.E. Higgins (Foto: Glenda Mendieta‐Leiva), Lower right corner: Anthurium formosum Schott (Photo: Lars Nauheimer), lower left corner from above to below and left to right: Mormodes skinneri Rchb.f. (Photo: Lars Nauheimer), Trichomanes sp (Photo: Florian A. Werner), Thibaudia harlingii Luteyn (Photo: Florian A. Werner), and Vriesea heliconioides (Kunth) Hook. ex Walp. (Photo: Lars Nauheimer).